Governance mechanisms in multi-tier supply chains: a multiple case study in the Brazilian orange chain - Maia, Laís Moltene (2024)
Ensuring operational standards throughout a multi-tier supply chain challenging. Therefore, buyers must understand and manage the different levels of their chain, considering their first and second-tier suppliers. For this, the adoption of different governance mechanisms (contractual and relational) is essential for efficient supply chain management, avoiding illegal subcontracting, violations, and fraud. However, to date, no study has analyzed how different tiers in a supply chain use governance mechanisms among themselves to implement traceability. Moreover, there is a lack of studies that evaluate how traceability increases the transparency and reliability of information, improving supply chain governance. The aim of this study is to understand how different tiers have been using governance mechanisms to ensure the traceability in a multi-tier food supply chain. To achieve this objective, a multiple case study was carried out in two orange juice supply chains in the state of São Paulo. The data analysis compiled the governance mechanisms into 8 contractual mechanisms and 5 relational mechanisms. It was found that buyers use contractual (monitoring, certification, auditing, training) and relational (cooperation and coalition) mechanisms to guarantee the traceability process of their products. Another finding is that the buyer in these cases does not put efforts or resources into implementing traceability throughout the chain since the juice processor (1st tier) already does it in order to meet international standards. Another conclusion of the study was that traceability is a contractual governance mechanism.